(untitled) (Sains Humanika, 2018)
The purpose of this research is to survey the reaction of Malay Language teachers in normal primary schools towards the application of Higher Order Thinking Skills (HOTS) from the aspect of execution of HOTS in essay writing, confidence in delivery, difficulties experienced during delivery, the level used during delivery and the steps taken to overcome said problems after the teaching process of essay writing. Two male and female teachers teaching at a school in the district of Petaling Jaya were involved as participants in this research. This research was carried out using qualitative methods i.e. the case study and findings were elicit through conversation. Using conversation, the findings of the research show that the main method used by the participants in the application of HOTS were I-Think maps, Question & Answer (Q&A) sessions and high level difficulty questions. Meanwhile, the least used methods were brainstorming and project-based discussions. The participants of the research also displayed high level confidence in the usage of HOTS, but some problems did arise caused by varied intelligence of the students in a certain class causing some disturbance. The problem could be overcame by diversifying methods in delivering HOTS during teaching essay writing. Through this research also, it is found that the teachers use different standards between weak and excellent students, depending on the level of maturity in thinking. This research is significant in order to increase the application of higher order thinking skills in teaching Ujian Penilaian Sekolah Rendah (UPSR) level essays by Bahasa Melayu teachers.